Human rights - Spencer, Maureen, 1941- (Nutshells, 2007)
'Nutshells' presents the basic facts and key principles of the important cases in each area of law, in clear and straightforward language. Cases are organised by topic areas illustrating key principles of the law. This edition includes revised sections on privacy and employment rights